(untitled) (Global Journal of Management and Business Research, 2013)
Our life will remain incomplete without media. The radio, television, newspaper and internet are some forms through which we get information. The common people believe the news given by the media. So, the media should be very careful before giving any news to the public. Aim of the study to check the public perception about media. The research population consist mostly on the students, because we want to check the perception of public about media and our easily reachable public target is our university and we also target the employed people, self-own businessmen and household’s women. We used the approach simple random sampling. Our research that we conducted on the impact of media in response to our objectives mostly people are agree with our statements and encourage our topic and research.